Comparison of heparinized saline and 0.9% sodium chloride for maintaining peripheral intravenous catheter patency in dogs. (9th September 2013) - Ueda, Yu; Odunayo, Adesola; Mann, F.A.
Abstract Objective To determine whether heparinized saline would be more effective in maintaining the patency of peripheral IV catheters in dogs compared to 0.9% sodium chloride. Design Prospective blinded randomized study. Setting University Veterinary Teaching Hospital. Animals Thirty healthy purpose bred dogs, intended for use in the junior surgery laboratory, were utilized. The dogs were randomized into 1 of 3 groups, 2 treatment groups and a control group. Interventions An 18‐Ga cephalic catheter was placed in the cephalic vein of each dog. Each dog in the treatment group had their catheter flushed with either 10 IU/mL heparinized saline or 0.9% sodium chloride every 6 hours for 42 hours. The dogs in the control group did not have their catheters flushed until the end of the study period. Immediately prior to flushing catheters, each catheter was evaluated for patency by aspiration of blood and the catheter site was evaluated for phlebitis. Measurements and Main Results All dogs in the heparinized saline and 0.9% sodium chloride group had catheters that flushed easily at each evaluation point. More dogs in the saline group had catheters from which blood could not be aspirated, but there was no significant difference between these groups. All dogs in the control group had catheters that flushed easily at the end of the assigned 6 hour interval except in 1 dog. Phlebitis was not detected in any dog. Conclusions Flushes of 0.9% sodium chloride were found to be as effective as 10 IU/mL heparinized saline flushes in maintaining patency of 18‐Ga peripheral venous catheters in dogs for up to 42 hours. For peripheral catheters placed with the intention of performing serial blood draws, heparinized flushes may be warranted.